Analysis of Nursing Care for Patients with Impaired Skin Integrity by Providing Back Massage in Intracerebral Hemorrage Cases - Zahro, Siti Fatimatus; Murtaqib, Murtaqib; Sutawardana, Jon Hafan; Mustakim, Mustakim (UPT Percetakan dan Penerbitan Universitas Jember, 2024)
Intracerebral Hemorrhage (ICH) occurs due to the presence of cerebral hemorrhage as a result of rupture of blood vessels in the brain tissue. Clinically Intracerebral Hemorrhage can be characterized by the presence of a decrease in consciousness. So that bed rest is one of a person's efforts in restoring his condition by lying in bed for a long time. It is at risk for experiencing impaired skin integrity. One of the skin integrity disorders that occurs in clients with bed rest is a decubitus ulcer. Skin care is one of the efforts to improve pressure sores by providing back massage therapy. This study aimed to analyze the nursing care of Skin Integrity Disorder patients by giving back massage in ICH cases in the Jasmine room of Dr. Soebandi Jember Hospital. The design of this study is descriptive in the form of a case study in patient who experienced redness of the skin of his back due to prolonged bed rest. After being given a back massage for 2 x 24 hours for 3 days, the patient experienced a change in skin integrity as evidenced by reduced redness of the skin. The administration of back massage therapy is effective in reducing the problem of skin integrity disorders in intracerebral hemorrhage patients who are lying down